Attraction and employer branding in IT companies - Lopes, Guilherme Filipe Martins (2021)
We live in the digital age where innovation happens daily prompted by technology. The discussion between start-ups and big companies is more present than ever in IT companies, especially when start-ups are growing at incredible pace and changing the industry. This study aims to bring clarity in the uncharted territory of Employer Branding and Talent Attraction in these companies. Mainly by understanding how these practices influence IT workers’ job search process and if there's a significant difference. The study relied on the analysis of questionnaire answers from 96 respondents that are IT workers using statistics to bring some clarity and methodical approach to the study. The obtained results show that although Employer Branding impacts job search, the type of culture doesn’t affect the job search process and it’s rather seen as an individual preference. This study settled a framework that can be used for further and deeper research that can be extremely influential and used as an instrument for organizations.